Public Institutional and Accountability in the Large Cooperative Sector in Chile - Díaz, Alejandro Andrés (2025)
Through this study, the performance of cooperative entities in Chile regarding accountability, specifically in the practices of financial report publication, has been assessed. The study focuses on the so-called economically significant cooperatives, employing a mixed research method that combines techniques from qualitative research such as documentary analysis and interviews, along with quantitative research techniques involving the construction of compliance indicators related to accountability. The research spans a period of eight years, from 2015 to 2022. The main finding of the study is that, despite the considerable dynamism in Chile’s institutional framework regulating and promoting cooperative sector activities since 2013, cooperatives exhibit a low level of compliance in terms of publishing their financial statements.